Teaching early years foundation stage - Basford, Jo.; Hodson, Elaine; Sage eBooks (Exeter : Learning Matters, 2008)
This title examines the continuous nature of learning from birth to five, the inter-relatedness between care, learning and development, and the importance of sensitive transitions.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: Early childhood education; Preschool teaching; Electronic books